A Note on Opening of Eyes of Some Great Cat Cubs in Captivity - Acharjyo, L. N.; Misra, R. (Indian Forester, 1972)
This note deals with some observations on the age at which the eyes of three kinds of new born great cat cubs opened at the Nandankanan biological park (Orissa). It has been observed that the tiger cubs open their eyes in seven to eleven days, African lion cubs open their eyes in thirteen to fourteen days and the leopard cubs open their eyes in eight to fifteen days. The available data has been cited and discussed.